Kinerja Demonstrasi Prototype Alat Early Warning System Erosi di Desa Dalangan - Fendi Hary Yanto; Jupiter Reva Anton; Anindita Radya Naila; Chintya Audrey Margaretha Silaen; Intan Kusumaning Jati; Recalliandra Marella Zainenci; Artdea Putri; Naufal Rizky Sayyid; Ratna Utami; Fauziah Imma Rohmatullaili; Sabrina Fatihaturrizky (Pusat riset dan Inovasi Nasional, 2023)
Erosion is a serious problem in riverbank areas. This is because erosion is the starting point for subsequent natural disasters such as landslides. Based on this understanding, empowerment is needed by installing an Early Warning System, mapping of vulnerable areas and evacuation routes, as well as outreach aimed at increasing the understanding and awareness of residents for mitigation. The early warning system socialization program is carried out with Focus Group Discussions so that it can run interactively. Thus, it is hoped that there will be an increase in public understanding and awareness of natural disasters, as well as an increase in the quality of community empowerment by students in the implementation of applied science.